The Transplant Palliative Care Clinic: An early palliative care model for patients in a transplant program. Issue 12 (4th November 2016) - Wentlandt, Kirsten; Dall'Osto, Angela; Freeman, Nicole; Le, Lisa W.; Kaya, Ebru; Ross, Heather; Singer, Lianne G.; Abbey, Susan; Clarke, Hance; Zimmermann, Camilla
Abstract: Although patients within a transplant program are awaiting or have received disease modifying or curative treatment, they are also facing advanced illness and the possibility of death. The involvement of specialized palliative care services for these patients may improve symptom management and facilitate advance care planning. However, patients in organ transplantation programs have difficulty accessing palliative care resources and often do so only sporadically in the inpatient setting. Currently, there is little access to ambulatory palliative care for these patients and there have been no descriptions of programs delivering such care in the medical literature. We outline the development and structure of a Transplant Palliative Care Clinic within the University Health Network's Multi‐Organ Transplant Program, in Toronto, Canada. This information may be helpful for others aiming to provide early, integrated palliative care to patients awaiting and receiving organ transplantation.